2000
DOI: 10.1002/(sici)1097-4547(20000601)60:5<686::aid-jnr14>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and ?-aminobutyric acid content and release of synaptosomes from temporal lobe epilepsy patients

Abstract: During surgical intervention in medically refractory temporal lobe epilepsy (TLE) patients, diagnosed with either mesial temporal lobe sclerosis (MTS)- or tumor (T)-associated TLE, biopsies were taken from the anterior temporal neocortex and the hippocampal region. Synaptosomes, isolated from these biopsies were used to study intrasynaptosomal Ca(2+) levels ([Ca(2+)](i)), and glutamate and gamma-aminobutyric acid (GABA) contents and release. All synaptosomal preparations demonstrated a basal [Ca(2+)](i) of abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Therefore, we cannot exclude that findings might be different in regions of epileptic cortex. Nevertheless, Hoogland et al, (2000) found the GABA content in synaptosomes from neocortical projection areas to be reduced to the same extent in patients with temporal lobe epilepsy (TLE) with and without tumor. In agreement with a study measuring effects of vigabatrin on brain GABA (Mueller et al, 2003) the presence of structural abnormality or its type does not seem to influence the occipital GABA levels found at baseline or in response to LEV.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we cannot exclude that findings might be different in regions of epileptic cortex. Nevertheless, Hoogland et al, (2000) found the GABA content in synaptosomes from neocortical projection areas to be reduced to the same extent in patients with temporal lobe epilepsy (TLE) with and without tumor. In agreement with a study measuring effects of vigabatrin on brain GABA (Mueller et al, 2003) the presence of structural abnormality or its type does not seem to influence the occipital GABA levels found at baseline or in response to LEV.…”
Section: Discussionsupporting
confidence: 89%
“…A deficiency in glutamine synthesis in astrocytes, found by several authors 22 , can also explain the high levels of glutamate in extracellular space, suggesting increased release of this amino acid. Working with synaptosomes from hippocampus of patients with TLE and MTS, was found 23 increased basal release of glutamate and GABA, data that could support our findings. Thus, the decreased concentration found in sclerotic hippocampus could be associated to increased release of this neurotransmitter, as already reported by several authors.…”
Section: Discussionsupporting
confidence: 87%
“…Two-photon uncaging produces excited states exactly as UV excitation does while also overcoming major limitations when probing biological tissue, such as spatial resolution, tissue penetration, and toxicity [73]. Two-photon uncaging is of special interest in epilepsy research, as imbalances between excitatory (glutamatergic) and inhibitory (GABAergic) neurotransmission have been implicated in the pathogenesis of the disorder [27,28,74]. Uncaging is used in four of the studies included in this review.…”
Section: Two-photon Imagingmentioning
confidence: 99%
“…When probing molecular environments wherein intensity-based measurements alone are often insufficient, fluorescence lifetime-based measurements may be capable of yielding additional data [26]. Finally, the development of a wide range of fluorescent markers has made it possible to study various aspects of the pathophysiology of epilepsy, such as neurotransmitter levels [27,28], metabolism [28,29], pathological neuronal activity [27], and hypersynchronous network firing [30].…”
Section: Introductionmentioning
confidence: 99%